Criminal Justice and Security in Central and Eastern Europe: Perspectives of Rural Safety, Security and Rural Criminology, Book of Abstracts - Marina Bajić; Meško, Gorazd; Dobovšek, Bojan; Tominc, Bernarda (2021)
Conference proceedings consist of abstracts of conference papers presented at the 13th international biennial conference on Criminal Justice and Security in Central and Eastern Europe organised by the Faculty of Criminal Justice ans Security of the University of Maribor, Slovenia. The conference was held online between 13 and 15 September 2021. A lead topic of the conference is rural criminology and perspectives such as deviance, crime and social control activities, and provision of safety ans security. At the conference, 68 papers were presented by 116 authors from 22 countries. A celebration of the 25th anniversary of the international biennial conference took place. The conference proves an active and fruitfull international research activities of the Faculty of Criminal Justice and Security of the University of Maribor.
Keywords: criminal justice; criminal justice and security studies; criminology; conference; Central and Eastern Europe; rural criminology